Antistatic flame-retardant release paper and preparation method thereof

By using modified PET and other materials and surface modification technologies in high-temperature resistant release paper, the paper's anti-static, flame retardant and strength performance is enhanced, and the problem of insufficient comprehensive performance of existing high-temperature resistant release paper is solved, achieving more efficient anti-stick and protection effects.

CN119913781APending Publication Date: 2025-05-02JIANGSU CHENXU NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411955759.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-28
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

While existing high-temperature resistant release papers are resistant to high temperatures, their performance in other aspects such as electrostatic function, flame retardant effect and lifting degree are insufficient, and their overall performance is insufficient.

Method used

Anti-static flame-retardant release paper including paper, release film, adhesive layer and anti-static flame-retardant film are used. The paper consists of deinked waste pulp, plant crushing slag, waste fiber, magnesium silicate and calcium carbonate. The anti-static flame-retardant film uses modified PET, oxidized starch, vinyl acetate-ethylene copolymer emulsion and other materials. Through technical means such as surface modification and enzymatic treatment, the strength, flame-retardant effect and anti-static properties of the paper are enhanced.

Benefits of technology

It achieves comprehensive performance of anti-static, flame retardant and high-strength, improving the paper's high temperature resistance, anti-stickness and protection effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses antistatic flame-retardant release paper and a preparation method thereof, and relates to the technical field of release paper. The antistatic flame-retardant release paper comprises paper, a release film, an adhesion layer and an antistatic flame-retardant film, and the paper comprises the following components in parts by weight: 60-80 parts of deinked waste paper pulp, 30-40 parts of plant crushed residues, 5-16 parts of waste fibers, 10-20 parts of magnesium silicate, 10-20 parts of calcium carbonate and 20-25 parts of ethylene glycol; the release film is prepared from the following components in parts by weight: 1 to 3 parts of polyethylene wax particles, 20 to 30 parts of palm oil, 20 to 40 parts of vinyl-terminated organosilicon resin, 20 to 30 parts of ethyl acetate, 6 to 15 parts of acrylate monomers, 0.5 to 1.5 parts of an initiator, 20 to 30 parts of ethylene glycol monomethyl ether and 1 to 3 parts of an initiator; the antistatic flame-retardant film is prepared from the following components in parts by weight: 40 to 60 parts of modified PET, 8 to 12 parts of oxidized starch, 8 to 12 parts of vinyl acetate-ethylene copolymer emulsion, 1 to 5 parts of graphene oxide, 4 to 8 parts of needle-like titanium dioxide, 4 to 8 parts of ferroferric oxide microspheres and 15 to 20 parts of diethylene glycol.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of release paper, in particular to an anti-static and flame-retardant release paper and a preparation method thereof. Background Art

[0002] Release paper is also called isolation paper, anti-sticking paper, and silicone oil paper. It is a kind of anti-sticking paper that prevents the prepreg from sticking and protects the prepreg from contamination. High temperature resistant release paper can be used to make synthetic leather and artificial leather with different temperature requirements. Domestic research on high temperature resistant release paper has been carried out for a long time, and there are also release papers that can withstand high temperatures of 200 degrees Celsius. However, these release papers are not as resistant to high temperatures, but lack other performances, such as lack of electrostatic function, lack of flame retardant effect, or insufficient tensile strength and comprehensive performance. Summary of the invention

[0003] The object of the present invention is to provide an anti-static and flame-retardant release paper and a preparation method thereof, so as to solve the problems existing in the prior art.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: an anti-static flame-retardant release paper, comprising paper, a release film, an adhesive layer, and an anti-static flame-retardant film, wherein the paper comprises, by weight, 60 to 80 parts of deinked waste paper pulp, 30 to 40 parts of crushed plant residue, 5 to 16 parts of waste fiber, 10 to 20 parts of magnesium silicate, 10 to 20 parts of calcium carbonate, and 20 to 25 parts of ethylene glycol; The release film comprises, by weight, 1 to 3 parts of polyethylene wax particles, 20 to 30 parts of palm oil, 20 to 40 parts of vinyl-terminated silicone resin, 20 to 30 parts of ethyl acetate, 6 to 15 parts of acrylic acid ester monomers, 0.5 to 1.5 parts of initiator, and 20 to 30 parts of ethylene glycol methyl ether; The adhesive layer is one of a water-based polyethylene coating layer and a water-based polypropylene coating layer, and the thickness of the adhesive layer is 60-300 nm; The antistatic flame retardant film comprises, by weight, 40-60 parts of modified PET, 8-12 parts of oxidized starch, 8-12 parts of vinyl acetate-ethylene copolymer emulsion, 1-5 parts of graphene oxide, 4-8 parts of needle-shaped titanium dioxide, 4-8 parts of ferrosoferric oxide microspheres, 15-20 parts of diethylene glycol, and 1-3 parts of initiator; the film layer thickness is 0.5-5 μm; The preparation method of the modified PET is as follows: water, anhydrous ethanol and dichloromethane are mixed in a mass ratio of 28-33:40-55:7-32, stirred at 500 rpm for 30 minutes, 2-aminotoluene-4-sulfonic acid, bis(4-aminophenyl) phosphate and 2-allylaniline are added in a mass ratio of 1-3:3:0.5-1.0, the mass ratio of 2-aminotoluene-4-sulfonic acid to water is 1:10-20, stirred at 25°C and 80 rpm, ammonium persulfate is added, and the molar ratio of 2-aminotoluene-4-sulfonic acid to ammonium persulfate is (1 ~3): 1. react for 3 hours, filter, wash the filter cake with ethanol and deionized water for 6 times, and dry at 60°C for 24 hours to obtain flame-retardant polyaniline; by weight, 10-25 parts of flame-retardant polyaniline and 60-85 parts of polyethylene terephthalate particles are mixed uniformly, and then blended, extruded, cooled and pelletized through a screw extruder; the temperature of the feeding section of the twin-screw extruder is 200°C, the temperature of the melt plasticizing section is 260°C, and the die temperature is 260°C; the intrinsic viscosity of the polyethylene terephthalate selected in the present invention is 0.65dL / g.

[0005] 2. The anti-static flame-retardant release paper according to claim 1 is characterized in that the magnesium silicate is also surface-modified by an amino coupling agent, and the specific steps are: adding magnesium silicate to toluene, ultrasonically dispersing it uniformly, then adding an aminosilane coupling agent, reacting it at 80-110° C. for 10-15 hours, filtering it after the reaction, repeatedly washing it with ethanol and deionized water, and drying it, wherein the usage ratio of magnesium silicate, toluene and aminosilane coupling agent is 1g: (0.05-0.1)L: (0.5-2)g.

[0006] 3. The anti-static flame-retardant release paper according to claim 2, characterized in that the amino coupling agent is at least one of aminopropyltrimethoxysilane, N-(2-aminoethyl-3-aminopropyl)methyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, and 3-aminopropyltriethoxysilane.

[0007] 4. The anti-static and flame-retardant release paper according to claim 1, characterized in that the basis weight of the paper is 70-80 g / m 2 .

[0008] 5. The anti-static and flame-retardant release paper according to claim 1, characterized in that the plant crushed residue is straw and plant stems that are ultra-finely crushed to 400 meshes.

[0009] 6. The anti-static flame-retardant release paper according to claim 1 is characterized in that the paper comprises the following preparation steps: mixing deinked waste paper pulp and plant crushed residue, adding cellulase, the cellulase accounting for 1-3% of the mass of the plant crushed residue, hydrolyzing at 30°C for 5 hours, adding waste fiber, magnesium silicate, calcium carbonate, and ethylene glycol, beating at 100°C for 30 minutes, cooling to room temperature while beating, and placing in a paper sheet former to form a wet paper blank; placing the wet paper blank in a hot press for hot pressing and drying, the hot pressing conditions are 15-25MPa, 10 minutes, and the drying conditions are vacuum degree 0.01-0.02MPa and temperature 90-110°C.

[0010] 7 . The anti-static and flame-retardant release paper according to claim 1 , wherein the release film has a thickness of 60-300 nm.

[0011] 8. The anti-static flame-retardant release paper according to claim 1, characterized in that the acrylic ester monomer is a mixture of one or more of isooctyl methacrylate, butyl acrylate, glycidyl methacrylate, and hydroxyethyl acrylate; and the initiator is one or more of azobisisobutyronitrile, azobisisoheptylnitrile, benzoyl peroxide, tert-butyl perbenzoate, and dicumyl peroxide.

[0012] 10. The anti-static flame-retardant release paper according to claim 1 is characterized in that the graphene oxide, needle-shaped titanium dioxide, and ferrosoferric oxide microspheres are also surface-modified with allyltrimethoxysilane, and the specific steps are: respectively immersing the graphene oxide, needle-shaped titanium dioxide, and ferrosoferric oxide microspheres in a 1.5 vol% allyltrimethoxysilane-ethanol solution at a mass ratio of 0.13 g / mL, immersing for 1 hour, and then drying.

[0013] Compared with the prior art, the beneficial effects achieved by the present invention are: (1) The paper used in the present invention uses waste fibers, waste paper pulp after deinking and plant crushing residue as raw materials. The raw materials are widely available and waste is turned into treasure. In the mixing stage of waste paper pulp and plant crushing residue, enzymatic hydrolysis is carried out to effectively separate different cellulose components in the raw materials. By relying on environmental solvents, cross-linking is strengthened to enhance the strength of the paper. The added waste fibers are also pulped to enhance the swelling effect of waste paper pulp on the fibers, thereby enhancing the bonding force between the fibers and cellulose when the paper is formed, thereby achieving the purpose of improving the strength of the paper. In addition, in the paper preparation process, magnesium silicate and calcium carbonate are added. The surface of magnesium silicate is modified with amino functional groups, and calcium carbonate has a certain hydrophilicity. No binder is required. Magnesium silicate and calcium carbonate form intermittent distribution of strong / weak bonds on the surface of cellulose, which can achieve uniform distribution and improve the strength, fracture toughness and flame retardant effect of the paper. (2) The present invention adopts flame-retardant polyaniline modified PET as the surface protective film of release paper. Flame-retardant polyaniline is an aromatic compound with good thermal stability and good compatibility when blended with PET, thereby being able to achieve the purpose of modifying PET. Flame-retardant polyaniline contains multiple elements such as N, P, and S, which achieve a synergistic flame retardant effect and effectively improve the flame retardant effect of release paper. At the same time, oxidized starch is compounded to enable the PET film layer to form a continuous and dense carbon layer when encountering fire, so as to more effectively protect the internal matrix. In addition, conductive fillers of different forms are added to the PET film, which can form a three-dimensional conductive path through chemical bonding with the flame-retardant polyaniline, thereby optimizing the antistatic effect of the release paper. DETAILED DESCRIPTION

[0014] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Example 1

[0015] An anti-static flame-retardant release paper, comprising paper, a release film with a thickness of 200 nm, an adhesive layer, and an anti-static flame-retardant film, wherein the basis weight of the paper is 80 g / m 2 The paper comprises, by weight, 60 parts of deinked waste pulp, 30 parts of plant shredded residue, 5 parts of waste fiber, 10 parts of magnesium silicate, 10 parts of calcium carbonate, and 20 parts of ethylene glycol; The release film comprises, by weight, 1 part of polyethylene wax particles, 20 parts of palm oil, 20 parts of vinyl-terminated silicone resin, 20 parts of ethyl acetate, 6 parts of glycidyl methacrylate, 0.5 parts of initiator, and 20 parts of ethylene glycol methyl ether; the molar percentage of vinyl in the vinyl-terminated silicone resin is 0.5%; The adhesive layer is one of a water-based polyethylene coating layer and a water-based polypropylene coating layer, and the thickness of the adhesive layer is 200 nm; The antistatic flame retardant film comprises, by weight, 40 parts of modified PET, 8 parts of oxidized starch, 8 parts of vinyl acetate-ethylene copolymer emulsion, 1 part of graphene oxide, 4 parts of needle-shaped titanium dioxide, 4 parts of ferroferric oxide microspheres, 15 parts of diethylene glycol, and 1 part of initiator; the film layer thickness is 2.5 μm; the viscosity of the vinyl acetate-ethylene emulsion is 4500 cps, and the solid content is 55%; The preparation method of the modified PET is as follows: water, anhydrous ethanol and dichloromethane are mixed in a mass ratio of 28:40:7, stirred at 500 rpm for 30 minutes, 2-aminotoluene-4-sulfonic acid, bis(4-aminophenyl) phosphate and 2-allylaniline are added in a mass ratio of 1.5:3:0.8, the mass ratio of 2-aminotoluene-4-sulfonic acid to water is 1:15, ammonium persulfate is added at 25°C and 80 rpm, the molar ratio of 2-aminotoluene-4-sulfonic acid to ammonium persulfate is 2:1, and the reaction is carried out. The mixture was stirred for 3 hours, filtered, and the filter cake was washed 6 times with ethanol and deionized water, and dried at 60°C for 24 hours to obtain flame-retardant polyaniline; 20 parts of flame-retardant polyaniline and 78 parts of polyethylene terephthalate particles were mixed uniformly by weight, and then blended, extruded, cooled and pelletized by a screw extruder; the temperature of the feeding section of the twin-screw extruder was 200°C, the temperature of the melt plasticizing section was 260°C, and the die temperature was 260°C; the intrinsic viscosity of the polyethylene terephthalate selected in the present invention was 0.65dL / g; The magnesium silicate is also surface-modified using an amino coupling agent, and the specific steps are: adding magnesium silicate to toluene, ultrasonically dispersing it uniformly, then adding aminopropyltrimethoxysilane, reacting it at 100° C. for 10 hours, filtering it after the reaction, repeatedly washing it with ethanol and deionized water, and drying it, wherein the usage ratio of magnesium silicate, toluene and aminosilane coupling agent is 1g:0.1L:2g.

[0016] The plant crushed residue is obtained by ultra-finely crushing straw and plant stems to 400 meshes; The paper comprises the following preparation steps: mixing deinked waste paper pulp and plant crushed residue, adding cellulase, wherein the cellulase accounts for 1% of the mass of the plant crushed residue, hydrolyzing at 30°C for 5 hours, adding waste fiber, magnesium silicate, calcium carbonate and ethylene glycol, beating at 100°C for 30 minutes, cooling to room temperature while beating, and placing in a paper sheet former to form a wet paper blank; placing the wet paper blank in a hot press, hot pressing and drying, wherein the hot pressing conditions are 15MPa and 10 minutes, and the drying conditions are vacuum degree 0.01MPa and temperature 90°C; The graphene oxide, needle-shaped titanium dioxide, and ferrosoferric oxide microspheres are also surface-modified with allyltrimethoxysilane, and the specific steps are: respectively immersing the graphene oxide, needle-shaped titanium dioxide, and ferrosoferric oxide microspheres in a 1.5 vol% allyltrimethoxysilane-ethanol solution at a mass ratio of 0.13 g / mL, immersing for 1 hour, and then drying. Example 2

[0017] The difference between Example 2 and Example 1 is that: the paper comprises 65 parts of deinked waste pulp, 32 parts of plant crushed residue, 8 parts of waste fiber, 12 parts of magnesium silicate, 12 parts of calcium carbonate, and 22 parts of ethylene glycol by weight; the release film comprises 1 part of polyethylene wax particles, 22 parts of palm oil, 25 parts of vinyl-terminated silicone resin, 22 parts of ethyl acetate, 9 parts of isooctyl methacrylate, 0.5 parts of initiator, and 22 parts of ethylene glycol methyl ether by weight; the anti-static flame-retardant film comprises 45 parts of modified PET, 8 parts of oxidized starch, 8 parts of vinyl acetate-ethylene copolymer emulsion, 2 parts of graphene oxide, 5 parts of needle-shaped titanium dioxide, 5 parts of ferrosoferric oxide microspheres, 17 parts of diethylene glycol, and 1 part of initiator by weight; and the remaining steps are the same as Example 1. Example 3

[0018] The difference between Example 3 and Example 1 is that: the paper comprises 70 parts of deinked waste pulp, 35 parts of plant crushed residue, 10 parts of waste fiber, 15 parts of magnesium silicate, 15 parts of calcium carbonate, and 22 parts of ethylene glycol by weight; the release film comprises 2 parts of polyethylene wax particles, 25 parts of palm oil, 30 parts of vinyl-terminated silicone resin, 25 parts of ethyl acetate, 10 parts of glycidyl methacrylate, 1 part of initiator, and 25 parts of ethylene glycol methyl ether by weight; the anti-static flame-retardant film comprises 50 parts of modified PET, 10 parts of oxidized starch, 10 parts of vinyl acetate-ethylene copolymer emulsion, 3 parts of graphene oxide, 6 parts of needle-shaped titanium dioxide, 6 parts of ferrosoferric oxide microspheres, 18 parts of diethylene glycol, and 2 parts of initiator by weight; the remaining steps are the same as Example 1. Example 4

[0019] The difference between Example 4 and Example 1 is that the paper comprises 80 parts of deinked waste pulp, 40 parts of plant crushed residue, 16 parts of waste fiber, 20 parts of magnesium silicate, 20 parts of calcium carbonate, and 25 parts of ethylene glycol by weight; the release film comprises 3 parts of polyethylene wax particles, 30 parts of palm oil, 40 parts of vinyl-terminated silicone resin, 30 parts of ethyl acetate, 15 parts of glycidyl methacrylate, 1.5 parts of initiator, and 30 parts of ethylene glycol methyl ether by weight; the anti-static flame-retardant film comprises 60 parts of modified PET, 12 parts of oxidized starch, 12 parts of vinyl acetate-ethylene copolymer emulsion, 5 parts of graphene oxide, 8 parts of needle-shaped titanium dioxide, 8 parts of ferrosoferric oxide microspheres, 20 parts of diethylene glycol, and 3 parts of initiator by weight.

[0020] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that no waste fiber is added during the paper preparation process, and the rest of the preparation method and composition are the same as Example 1.

[0021] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that no plant crushed residue is added during the paper preparation process, and the rest of the preparation method and composition are the same as Example 1.

[0022] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that magnesium silicate is not added during the paper preparation process, and the rest of the preparation method and composition are the same as Example 1.

[0023] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that calcium carbonate is not added during the paper preparation process, and the rest of the preparation method and composition are the same as Example 1.

[0024] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that only ordinary PET is used, and the rest of the preparation method and composition are the same as Example 1.

[0025] Comparative Example 6 The difference between Comparative Example 6 and Example 1 is that graphene oxide, titanium dioxide, and ferrosoferric oxide are all in a flaky structure, and the rest of the preparation method and composition are the same as in Example 1.

[0026] Effect example The following Table 1 shows the performance analysis results of xxxxx using Examples 1 to 3 of the present invention and Comparative Examples 1 to xx.

[0027] Table 1

[0028] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. An anti-static flame-retardant release paper, comprising paper, a release film, an adhesive layer, and an anti-static flame-retardant film, characterized in that: The paper comprises, by weight, 60 to 80 parts of deinked waste paper pulp, 30 to 40 parts of crushed plant residue, 5 to 16 parts of waste fiber, 10 to 20 parts of magnesium silicate, 10 to 20 parts of calcium carbonate, and 20 to 25 parts of ethylene glycol; The release film comprises, by weight, 1 to 3 parts of polyethylene wax particles, 20 to 30 parts of palm oil, 20 to 40 parts of vinyl-terminated silicone resin, 20 to 30 parts of ethyl acetate, 6 to 15 parts of acrylic acid ester monomers, 0.5 to 1.5 parts of initiator, 20 to 30 parts of ethylene glycol methyl ether, and 1 to 3 parts of initiator; The adhesive layer is one of a water-based polyethylene coating layer and a water-based polypropylene coating layer, and the thickness of the adhesive layer is 60-300 nm; The antistatic flame-retardant film comprises, by weight, 40-60 parts of modified PET, 8-12 parts of oxidized starch, 8-12 parts of vinyl acetate-ethylene copolymer emulsion, 1-5 parts of graphene oxide, 4-8 parts of needle-shaped titanium dioxide, 4-8 parts of ferrosoferric oxide microspheres, and 15-20 parts of diethylene glycol; The modified PET is prepared by uniformly mixing flame-retardant polyaniline and polyethylene terephthalate particles, and then blending, extruding, cooling and pelletizing through a screw extruder.

2. The anti-static and flame-retardant release paper according to claim 1, characterized in that: The magnesium silicate is also surface-modified using an amino coupling agent.

3. The anti-static and flame-retardant release paper according to claim 2, characterized in that: The amino coupling agent is at least one of aminopropyltrimethoxysilane, N-(2-aminoethyl-3-aminopropyl)methyldimethoxysilane, γ-aminopropylmethyldiethoxysilane and 3-aminopropyltriethoxysilane.

4. The anti-static and flame-retardant release paper according to claim 1, characterized in that: The basis weight of the paper is 70-80 g / m 2 .

5. The anti-static and flame-retardant release paper according to claim 1, characterized in that: The plant crushed residue is obtained by ultra-finely crushing straw and plant stems to 400 meshes.

6. The anti-static and flame-retardant release paper according to claim 1, characterized in that: The paper comprises the following preparation steps: mixing deinked waste paper pulp and plant crushed residue, adding cellulase, hydrolyzing at 30°C for 5 hours, adding waste fiber, magnesium silicate, calcium carbonate and ethylene glycol, beating at 100°C for 30 minutes, cooling to room temperature while beating, placing in a paper sheet former to form a wet paper blank; placing the wet paper blank in a hot press for hot pressing and drying.

7. The anti-static and flame-retardant release paper according to claim 1, characterized in that: The release film has a thickness of 60-300 nm.

8. The anti-static and flame-retardant release paper according to claim 1, characterized in that: The acrylic ester monomer is a mixture of one or more of isooctyl methacrylate, butyl acrylate, glycidyl methacrylate, and hydroxyethyl acrylate; the initiator is one or more of azobisisobutyronitrile, azobisisoheptylnitrile, benzoyl peroxide, tert-butyl perbenzoate, and dicumyl peroxide.

9. The anti-static and flame-retardant release paper according to claim 1, characterized in that: The flame-retardant polyaniline is prepared by polymerizing 2-aminotoluene-4-sulfonic acid, bis(4-aminophenyl)phosphate and 2-allyl aniline.

10. The anti-static and flame-retardant release paper according to claim 1, characterized in that: The graphene oxide, needle-shaped titanium dioxide and ferroferric oxide microspheres are also surface-modified with allyltrimethoxysilane.